John Constantine, Hellblazer. [4] The family man - Delano, Jamie (DC Comics, 2012)
"Constantine attempts a vacation after recent events, but as usual, things don't go as planned. Plus, Constantine must uncover the mystery of the murderous Family Man."--Amazon.com.